RICE-FISH FARMING SYSTEM IN LAMONGAN, EAST JAVA, INDONESIA: SWOT AND PROFIT EFFICIENCY ANALYSIS - Dyah Retnani Nurhidayati; Wen-Chi Huang; Nuhfil Hanani; S Sujarwo (Agricultural Socio-Economics Journal, 2020)
The agricultural sector needs to make breakthroughs in the design of production systems to improve farmers' income and operation efficiency. One of the ways is to redesign rice production methods by applying a rice-fish farming system. Lamongan has a different system that combines rice cultivation with vannamei shrimp. Due to the limitation of farmers, the efficiency of the system has not yet reached the optimal level. This study describes the rice-fish farming system, identifies the SWOT and generated the grand strategy matrix, and analyzed the profit efficiency using Stochastic Frontier Analysis. The results showed that the strengths and opportunities are more influential, where the position was in the quadrant I; which means it is in a good strategic position. Meanwhile, the input factors which significantly influence profit where the cost of paddy seed, the cost of organic fertilizer, the cost of inorganic fertilizer, the cost of pesticide, and the cost of shrimp feed. The profit efficiency analysis shows that respondents engaged in this system did not efficiently allocate inputs and production cost factors appropriately. The average profit efficiency level was 78.05 percent; it means that there were still opportunities to increase profits from the system by 21.5 percent.